Pragmastylistic Features of Characters’ Speech in the Text of Fiction - Sargsyan, Mariana; Hakobyan, Gayane (Armenian Folia Anglistika, 2015)
Largely speaking, the present paper seeks to substantiate the role of the pragmastylistic analysis as a crucial tool for the study of relations between various levels of literary texts and to illustrate how the pragmatic and stylistic dimensions in the study of the literary texts can become an efficient extension to the traditional analytical toolkit. Our major objective is to expose the role of the character’s speech in the work of fiction, meanwhile observing those pragmastylistic resources employed by the author which contribute to the formation of the pragmatic meaning of the text and support the pragmatic impact on the reader.
Keywords: pragmastylistics; meaning; effect; characters’ speech; pragmastylistic resources and markers